Bioliquefaction of the extracts from Shengli lignite. (1st May 2018) - Yao, Jing-Hua; Xiao, Lei; Yan, Cong-Wei; Zhang, Yue; He, Huan; Wei, Xian-Yong; Wang, Yu-Gao
Highlights: Lignite was isolated and classified into simpler extracts with fractional extraction. Each extract was bioliquefied by fungus WF8 and the most easily bioliquefied extract was obtained and analyzed. The microbial liquefaction possibly involved in the cleavage of C–O–C and Si–O bonds to some extent. Abstract: Shengli lignite was sequentially extracted with aqueous NaOH solution, n -hexane, dichloromethane (DCM), isometric benzene and ethanol (IMBE), and acetone to obtain extracts 1–5 (E1 –E5 ). Each extract was biotreated by an isolated fungus WF8 under the same conditions. The results show that E1 is much more susceptible to the bioliquefaction (BL) than other extracts. The BL of E1 proceeded via the cleavage of C–O–C and Si–O bonds to some extent, while most of the methylaromatic and –COOH-containing moieties in E1 are inert toward BL by WF8. E1 has largely similar molecular mass distribution (MMD) to unliquefied E1, but quite different MMD from bioliquefied E1, further indicating that the BL of E1 proceeded via biochemical reactions by WF8.